METODOLOGI TAfSIR KONTEMPORER (STUDI KOMPARASI ATAS PEMIKIRAN fAzLUR RAHMAN DAN MUHAMMAD SYAHRUR) - Zulyadain Zulyadain (UIN Mataram, 2018)
The main problem of interpretation is actually the giving of meaning and production of meaning, however, there is a difference between Rahman and about the nature of interpretation, for Rahman the essence of interpretation is how an interpreter is able to fnd authentic meaning from a text through socio-historical context the past, then capture the moral ideal aspect to contextualize the meaning in the present era with a new methodology. While syahrur, interpretation does not have to be like that, an interpreter, does not have to determine authentic meaning (original meaning) in the past, but can only immediately search for the meaning of the relevant text in the presentnera, because that meaning can also develop according to contemporary scientifc reasoning. The Qur’an must be seen as if it had just come down yesterday and the Prophet had just greeted us. Thus, Fazlur Rahman and Muhammad Sharur are progressive fgures of Muslims who carry out reforms as well as deconstruction and reconstruction of the study of the Qur’an’s interpretation in the contemporary era. Both are concerned with the Islamic paradigm that touches reality, by offering new interpretations and methodologies to religious teachings, to produce more humanist teachings